Understanding the Interactions Between Cetaceans and Other Megafauna With the Albacore Tuna Fishery: A Case Study From the Cyprus’ Pelagic Longline Fishery - Papageorgiou, Marios; Hadjioannou, Louis; Jimenez, Carlos; Georgiou, Andreas; Petrou, Antonis (Frontiers in Marine Science, 2022)
Depredation by cetaceans on fisheries is a major issue globally, both in terms of conservation and fisheries economics. The present study conducted in Cyprus, Eastern Mediterranean Sea, aimed to understand the extent, level, and type of cetacean depredation on the albacore tuna pelagic longline fishery, and in particular to quantify and evaluate the economic consequences of depredation and identify potential dolphin-longline conflict areas and mitigation practices for management. The data were obtained from fisher’s logbooks, interviews and onboard observations between June and August 2018. A novel and simple approach was applied to estimate the depredation rate and economic loss by using simple calculations including the number and weight of depredated fish, landings and fishing effort. The results revealed that there is an estimated economic loss per fishing trip of 313.07± 486.19 EUR and an estimated annual economic loss for the entire fleet of 259,272 EUR from depredation caused by cetaceans. The study also estimated that 16,639 albacore tunas were depredated in 2018 and the depredation rate ranged between 0% to 100% with a mean depredation rate of 17% per fishing trip. Depredation by the common bottlenose dolphin and striped dolphin was reported in more than 50% of their fishing trips. Other species that were found to be involved in depredation were the neon flying squid, the shortfin mako shark and the Risso’s dolphin. This is the first official record worldwide of depredation from the common bottlenose dolphin, the striped dolphin and the neon flying squid on the pelagic longline albacore tuna fishery. A total bycatch of 62 individuals of common bottlenose dolphins and one individual of stripped dolphin were reported in interviews as a result of depredation on bait and catch. The study also identified depredation hotspots and possible depredation mitigation measures. Such information could support the development of management action plans and measures to minimise interactions between cetaceans and pelagic longlines.